Chronic Suppression of Periprosthetic Joint Infections with Oral Antibiotics Increases Infection-Free Survivorship. (5th August 2015) - Siqueira, Marcelo B.P.; Saleh, Anas; Klika, Alison K.; O'Rourke, Colin; Schmitt, Steven; Higuera, Carlos A.; Barsoum, Wael K.
Abstract : Background: The clinical benefit of chronic suppression with oral antibiotics as a salvage treatment for periprosthetic joint infection is unclear. The purpose of this study was to compare infection-free prosthetic survival rates between patients who received chronic oral antibiotics and those who did not following irrigation and debridement with polyethylene exchange or two-stage revision for periprosthetic joint infection. Methods: We reviewed the records on all irrigation and debridement procedures with polyethylene exchange and two-stage revisions performed at our institution from 1996 to 2010 for hip or knee periprosthetic joint infection. Of 625 patients treated with a total of 655 eligible revisions, ninety-two received chronic oral antibiotics for a minimum of six months and were eligible for inclusion in our study. These patients were compared with a matched cohort (ratio of 1:3) who did not receive chronic oral antibiotics. Results: The five-year infection-free prosthetic survival rate was 68.5% (95% confidence interval [CI] = 59.2% to 79.3%) for the antibiotic-suppression group and 41.1% (95% CI = 34.9% to 48.5%) for the non-suppression group (hazard ratio [HR] = 0.63, p = 0.008). Stratification by the type of surgery and the infecting organism showed a higher five-year survival rate for the patients in the suppression group who underwent irrigation and debridement with polyethylene exchange (64.7%) compared with those in the non-suppression group who underwent irrigation and debridement with polyethylene exchange (30.4%, p < 0.0001) and a higher five-year survival rate for the patients in the suppression group who had a Staphylococcus aureus infection (57.4%) compared with those in the non-suppression group who had a Staphylococcus aureus infection (40.1%, p = 0.047). Conclusions: Chronic suppression with oral antibiotics increased the infection-free prosthetic survival rate following surgical treatment for periprosthetic joint infection. Patients who underwent irrigation and debridement with polyethylene exchange and those who had a Staphylococcus aureus infection had the greatest benefit. Level of Evidence: TherapeuticLevel III . See the Instructions for Authors for a complete description of levels of evidence.